Clinical Skills Tutoring Program (CSTP): Developing a Curriculum for Medical Student Clinical Skills Peer Tutors - Chih-Chiun Jamie Chang; Sara-Megumi Rumrill; Abigail Phillips (Association of American Medical Colleges, 2022)
Introduction There are few curriculum materials designed to provide training and support for peer tutors to become effective clinical skills teachers. We designed the Clinical Skills Tutoring Program (CSTP) curriculum to guide tutors to help their students reflect on clinical skills performance, create an individualized learning plan, and engage in improvement based on feedback to achieve clinical skills competencies. Methods Curriculum content was delivered through an in-person training session, formal curriculum written content, online resources, and longitudinal support from faculty directors. Tutors (fourth-year medical students) received surveys to evaluate the in-person training session, curriculum resources, and overall program experience. Student participants (medical students of any year) completed a survey to rate their satisfaction in working with their tutors. Results There were 12 tutors in cohort 1 and 18 tutors in cohort 2. Survey response rates ranged from 50% to 70% among tutors. The tutors were satisfied with the in-person training session, program experience, curriculum resources, support from directors, development of learning goals with the student, and clinical skills practice with the student (mean Likert ratings greater than 4 out of 5). Student participants were satisfied with their experience creating learning goals and receiving feedback from their tutors. Discussion The tutor curriculum fills a gap by training and supporting tutors before and during their work with students needing further resources and remediation in one or more clinical skills domains. The curriculum can be implemented and further adapted by other tutoring programs locally and nationally.